Pengaruh Minuman Carica papaya L. terhadap Dismenore pada Remaja - Destariani, Elvi; Cesat, Sara; Effendi, Pauzan (Jurnal Sains & Kesehatan, 2024)
Dysmenorrhea is abdominal pain that occurs during menstruation, characterized by brief pain before or during menstruation. These pain complaints last one to several days during menstruation. This research aims to see the effect of Carica Papaya L drink on reducing dysmenorrhea. Method: pre-experimental research one group pretest-posttest without control group design. Population 220 people. A sample of 40 people was taken by using purposive sampling technique. Analysis used the Wilcoxon signed rank test. Results: Showed a decrease in dysmenorrhea after intervention with a mean difference of 3.85. Conclusion: There was an effect of Carica Papaya L drink on dysmenorrhea (p<0.05). It is hoped that Carica papaya L drink will become a non-pharmacological alternative for treating dysmenorrhea.